Analysis Of Taxation Motivation, Income Level, Tax Payment System, and Tax Sanctions On Compliance Of Land And Building Tax (PBB) Taxpayers (A Case Study In Waru District) - Revi Ardiana Putri; Sjarief Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of taxation motivation, income level, tax payment system, and tax sanctions on the compliance of Land and Building Tax (PBB) taxpayers in Waru District. Tax compliance is a critical factor in optimizing local revenue, and understanding the determinants that influence taxpayer behavior is essential for effective tax administration. The research employs a quantitative approach with data collected through questionnaires distributed to PBB taxpayers in Waru District. The data were analyzed using Smart PLS. The results of the study indicate that taxation motivation and tax sanctions have a significant positive effect on taxpayer compliance, while income level and the effectiveness of the tax payment system do not have an impact on Land and Building Tax (PBB) compliance. These findings suggest that increasing taxpayer awareness, simplifying payment procedures, and implementing consistent sanctions can enhance compliance with PBB payments. This study provides valuable insights for local governments in formulating strategies to encourage voluntary tax compliance.